Training deaf college students to improve their theory of mind: based on a two-component model - Wu, Yang; Liu, Xiping; Zhang, Shengnan (Frontiers in Psychology, 2024)
This paper explored the training methods to improve the level of deaf college students' ToM. Eighty deaf college students were selected as participants and randomly divided into experimental group and control group. The ToM training group received ToM training; The non-ToM training group received physical-conversation training. Cognitive ToM task and affective ToM task were used to investigate the training effect. After training, the level of ToM of deaf college students who received ToM training was significantly improved. The results show that ToM training can effectively promote the level of deaf college students' ToM.